Mechanisms of Epithelial Immunity Evasion by Respiratory Bacterial Pathogens - Sharma, Lokesh; Feng, Jingjing; Britto, Clemente J.; Dela Cruz, Charles S. (Frontiers in Immunology, 2020)
Bacterial lung infections are major healthcare challenges killing millions of people worldwide and resulting in a huge economic burden. Both basic and clinical research have elucidated host mechanisms that contribute to the bacterial clearance where an indispensable role of immune cells has been established. However, the role of respiratory epithelial cells in bacterial clearance has garnered limited attention due to their weak inflammatory or phagocytic ability compared to immune cells such as macrophages and neutrophils. These studies often underappreciate the fact that epithelial cells are the most abundant cells in the lung, not only serving as building blocks but also providing immune protection throughout the lung. Epithelial cells function either independently to eradicate the pathogen or communicate with immune cells to orchestrate pathogen clearance. The epithelial cells have multiple mechanisms that include mucus production, antimicrobial peptide production, muco-ciliary clearance and phagocytosis, all of which contribute to their direct antibacterial function. Secretion of cytokines to recruit immune cells and potentiate their antimicrobial activities is a pathway by which the epithelium contributes to bacterial clearance. Successful pathogens outsmart epithelial resistance and find a way to replicate in sufficient numbers to establish infections in the airway or lung epithelial surfaces. In this mini-review, we discuss evidences that establish important roles for epithelial host defense against invading respiratory bacterial pathogens and demonstrate how pathogens outsmart these epithelial immune mechanisms to successfully establish infection. Finally, we discuss briefly how to boost epithelial immunity to improve outcomes in bacterial lung infections.